2012
DOI: 10.1097/tp.0b013e31826032be
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Infiltrates and NFκB Subunit c-Rel Signaling in Kidney Allografts of Patients With Clinical Operational Tolerance

Abstract: Allografts from COT patients show significant cellular infiltrates but a distinct expression of proteins involved in the NFκB pathway and a higher proportion of forkhead box P3-positive cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…We have previously reported that CD4 + CD25 + FOXP3 + Treg-based mechanisms are likely to operate in our pediatric living-donor liver transplant (LDLT) recipients who could stop immunosuppression (IS) (referred to as 'operational tolerance' (OT) [5][6][7][8][9]. In support, a possible role of CD4 + CD25 + FOXP3 + Tregs in OT was reported by others in the settings of liver transplantation (Tx) and renal Tx [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 77%
“…We have previously reported that CD4 + CD25 + FOXP3 + Treg-based mechanisms are likely to operate in our pediatric living-donor liver transplant (LDLT) recipients who could stop immunosuppression (IS) (referred to as 'operational tolerance' (OT) [5][6][7][8][9]. In support, a possible role of CD4 + CD25 + FOXP3 + Tregs in OT was reported by others in the settings of liver transplantation (Tx) and renal Tx [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 77%
“…We previously demonstrated Nrf2‐mediated cytoprotective gene induction by a low level of anti‐HLA antibodies could promote acquisition of the resistance against complement‐mediated cytotoxicity . Recent findings suggested that NF‐kappaB was linked to kidney graft acceptance . Both transcription factors have been shown to be modulated through AMPK activation by resveratrol , which led us to hypothesize that AMPK activation might contribute accommodation under the complement‐ and thrombin‐mediated endothelial activated condition.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, the claim that an individual has become tolerant has to meet very stringent criteria [46]. [18] 1976 1 40 months Uehling [19] 1976 1 36 months Seigler (reply to Uehling) [19] 1976 1 > 4 years Zoller [20] 1980 14 1-8 years Strober [21,22] 1989 2 69 months and 12 years Burlingham [23,24] 1995 1 7 years Fischer [25] 1996 1 9 years Christensen [26] 1998 1 > 3 years Van Buskirk [27] 2000 2 § > 5 and > 27 years Cai [28] 2004 1 § 32 years Starzl [5] 2004 7 3-38 years University of Nantes, France [29,30] 2006 27 ‡ 2-20 years (one missing data) Xu [31] 2007 2 Not available Indices of Tolerance (IOT) [32] 2010 11 2-21 years Immune Tolerance Network (ITN) [33][34][35] 2010 39 Divided into 3 groups: (1) n 5 25, mean time: 16 6 10Á4 (2) n 5 7, mean time: 14 6 17Á1 (3) n 5 7, not available Azancot [36] 2011 2 ‡ 14 months and > 6 years Inal [37] 2011 1 8 years University of São Paulo, Brazil [38][39][40] 2012 5 1Á5-8 years Becker [41] 2012 4 1-19 years Roedder [42] 2014 69 Not available GAMBIT study [43,44] 2016 14 # 1 common 1-22Á5 years DESCARTES-Nantes Survey [8] 2016 40 # 1 common 1-25 years (5 missing data) Kesiraju [45] 2016 1 > 3 years Total 41 years of reports 247 -It is l...…”
Section: Defining An Enigma: the Need For Operational Criteriamentioning
confidence: 99%
“…A few histological examinations of tolerant allografts have been published [21,24,27,[29][30][31]36,41]. Biopsies from stable tolerant patients revealed lymphoid infiltrates in peritubular regions of the cortical interstitium, without tubulitis [41]. Such infiltrates are common in wellfunctioning allografts [66].…”
Section: Patient Descriptionmentioning
confidence: 99%